Perceptions of wood-processing industries on FLEGT implementation: Insights from Vietnam - Pham Thu Thuy; Tang, T.K.H.; Dang, T.T.N.; Tran, N.M.H.; Nguyen, T.T.A.; Nguyen, T.V.A.; Hoang, T.L.; Dang, H.P.; Nguyen, N.Q. (Elsevier, 2021)
This paper analyses timber and wood processing companies' views on opportunities and challenges for FLEGT implementation in Vietnam based on a literature review, online surveys with 56 timber and wood processing companies, in-depth interviews with 26 stakeholders from different institutions, and a consultation workshop involving 94 participants. Our paper shows that FLEGT has received increasing attention and political support from the Government of Vietnam, which has issued new policies on sustainable forest management, forest certification and financial incentives to enable timber and wood processing companies to participate in FLEGT. The active presence of civil society organizations has helped improve forest governance, which is a key aspect of FLEGT. Perceiving FLEGT as a global market trend able to generate higher profits, timber and wood processing companies see opportunities to benefit from this timber trading initiative, and are therefore more willing to comply with FLEGT requirements. However, these companies also highlight challenges to implementing FLEGT on the ground, including unclear and inconsistent policies, weak monitoring and evaluation, high transaction costs, companies' limited access to information, unclear tenure and erratic land-use planning, and the weak capacity of household and small-scale enterprises. Effective implementation of FLEGT requires regulatory changes, improved law enforcement and translation of policies on the ground, enhanced information exchange between stakeholders, and addressing underlying problems relating to land tenure and forest governance.